STRATEGIES FOR INDONESIAN SMES: EXPORT vs. PUBLIC PROCUREMENT IN THE POST-PANDEMIC ERA - Fitriana; Ricky Agusiady; Ijang Faisal (Journal of Jabar Economic Society Networking Forum, 2024)
The Indonesian government plays an important role in developing strategies to support SMEs in facing export and public procurement challenges in the post-pandemic era. This abstract discusses the main obstacles faced by Indonesian SMEs in accessing export markets and public procurement, as well as effective risk management strategies to increase their participation. First, challenges such as competition with large companies, complex bureaucracy, and limited access to information and business networks hinder SMEs from participating in the public procurement process. Second, risk management strategies such as forming consortia, increasing capacity through training, and active promotion can help SMEs overcome these obstacles. Third, the government needs to increase support through pro-SME policies, technical training, market promotion and infrastructure improvements to create a conducive business environment for SMEs. In this way, Indonesian SMEs will be able to increase their contribution to economic growth and national competitiveness.